2014
DOI: 10.12691/ijdsr-2-6a-4
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Plaque Removal Efficacy of Five Commercially Available Toothbrushes: A Comparative Clinical Study

Abstract: Background and Objectives-The aim of the study is to compare the plaque removal efficacy of five commercially available tooth brushes. Materials & Methods-The study group consisted of 75 subjects with age ranging 17 to 27 years distributed into five groups-Group A [Colgate Supershine], Group B [Colgate Zig zag], Group C [Oral B Allrounder], Group D [Oral B Fresh Clean], Group E [Pepsodent double action]. Study was single blinded, randomized clinical trial. Turesky-Gilmore-Glickmann Modification of Quigley-Hein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It has been reported that improved plaque removal, and therefore improved periodontal health, is associated with increasing the frequency of brushing to twice per day. 14 Therefore, cleaning three times per day or more does not appear to improve periodontal conditions further.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that improved plaque removal, and therefore improved periodontal health, is associated with increasing the frequency of brushing to twice per day. 14 Therefore, cleaning three times per day or more does not appear to improve periodontal conditions further.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pioneers of today's toothbrushes were developed in the 1930s. 3 The role of toothbrushes in preventing the initiation and progression of periodontal diseases has been well documented. The various designs of toothbrushes available in the market often put the common man in dilemma about the best design, and they often seek professional advice on this matter.…”
Section: Introductionmentioning
confidence: 99%